Study on the Reactivity of Mixed Carboxylic Palmitic Anhydrides via the Esterification Reaction Using Heterogeneous Catalyst - Derbel, Marwa; Trabelsi, Iteb; Essid, Kamel (Letters in Organic Chemistry, 2024)
>Lipid esters are prepared from mixed fatty anhydrides by esterification. These esters are high-value-added intermediates used in industrial applications. We describe the synthesis and characterization of esters using salicylic acid and mixed anhydrides with zinc oxide as catalysts. To achieve maximum reaction efficiency, we varied the mixed anhydride and studied some parameters in the reaction, such as the molar ratio (anhydride/alcohol) and the amount of catalyst. The esterification reaction was realized with some primary and secondary alcohols in the presence of resin Amberlyst- 15. The best yield of the palmitic ester was obtained in the case of mixed 4-chlorobenzoic palmitic anhydride. We obtained 53% of fatty ester. Moreover, we also studied the reactivity of certain mixed anhydrides for the esterification reaction of salicylic acid in the presence of a Lewis acid as a heterogeneous catalyst. The anhydrides were prepared in the presence of triethylamine in the organic solvent by a reaction between fatty acid and acid chloride. Mixed aromatic palmitic were more reactive and selective than the aliphatic anhydrides. The palmitic group was the most involved in acylation. Good yields of fatty esters were obtained with total conversion of mixed anhydrides.
Keywords: fatty ester